Description of the Attitude of Fulfilling the Spiritual Needs of the Elderly before Death - Fitriani, Alvita Desma; Setianingsih, Setianingsih; Darwati, Lestari Eko; Anggeraeni, Rina (Global Health Science Group, 2024)
Death in the elderly is a common occurrence, although most of the elderly are afraid of experiencing it. Therefore, mental and spiritual readiness is needed so that elderly people who are nearing death can die in a calm and peaceful state. Objective: to understand the description of the attitude of the elderly in fulfilling spiritual needs before death (meaning, goals and hopes of life, relationship with God and spiritual practices). Method: using descriptive survey design. The population was 105 respondents, taking 51 samples, using a simple random sampling technique. Sampling used simple random sampling. Results: research shows that the majority of elderly people are based on a median age of 68 years, are female (57%), have lived in an institution for >3 years (59%), suffer from degenerative diseases (63%), and have adequate compliance attitudes. spiritual needs of the elderly nearing death (98%). The elderly need to increase their actions to fulfill their spiritual needs to prepare for death calmly and peacefully.